Differential NtcA Responsiveness to 2-Oxoglutarate Underlies the Diversity of C/N Balance Regulation in Prochlorococcus - María A. Domínguez-Martín; Antonio López-Lozano; Rafael Clavería-Gimeno; Rafael Clavería-Gimeno; Rafael Clavería-Gimeno; Adrián Velázquez-Campoy; Adrián Velázquez-Campoy; Adrián Velázquez-Campoy; Adrián Velázquez-Campoy; Gerald Seidel; Andreas Burkovski; Jesús Díez; et al. (Frontiers in Microbiology, 2018)
Previous studies showed differences in the regulatory response to C/N balance in Prochlorococcus with respect to other cyanobacteria, but no information was available about its causes, or the ecological advantages conferred to thrive in oligotrophic environments. We addressed the changes in key enzymes (glutamine synthetase, isocitrate dehydrogenase) and the ntcA gene (the global nitrogen regulator) involved in C/N metabolism and its regulation, in three model Prochlorococcus strains: MED4, SS120, and MIT9313. We observed a remarkable level of diversity in their response to azaserine, a glutamate synthase inhibitor which increases the concentration of the key metabolite 2-oxoglutarate, used to sense the C/N balance by cyanobacteria. Besides, we studied the binding between the global nitrogen regulator (NtcA) and the promoter of the glnA gene in the same Prochlorococcus strains, and its dependence on the 2-oxoglutarate concentration, by using isothermal titration calorimetry, surface plasmon resonance, and electrophoretic mobility shift. Our results show a reduction in the responsiveness of NtcA to 2-oxoglutarate in Prochlorococcus, especially in the MED4 and SS120 strains. This suggests a trend to streamline the regulation of C/N metabolism in late-branching Prochlorococcus strains (MED4 and SS120), in adaptation to the rather stable conditions found in the oligotrophic ocean gyres where this microorganism is most abundant.